Enjoyment as a key to success? Links between e-tandem language learning and tertiary students’ foreign language enjoyment - Resnik, Pia; Schallmoser, Christine (Studies in Second Language Learning and Teaching, 2019)
This paper reports on crossing borders virtually via an e-Tandem scheme and presents the findings of a study, in which students of English from an Austrian university were paired with students of German from the UK and the USA. Drawing on data from 19 in-depth interviews, the study aims to identify links between e-Tandem language learning and foreign language enjoyment (FLE) (Dewaele & MacIntyre, 2014, 2016). A category-based qualitative text analysis (Kuckartz, 2014) revealed that a majority of the interviewees felt e-Tandem language learning contributed to their FLE. Furthermore, a range of reasons underlying students’ perceived enjoyment of learning a language in Tandem emerged: having authentic conversations in the target language with L1 (first language) users (Dewaele, 2018), perceiving each other as cultural mediators and a difference from language classroom contexts on the level of power relations, which made students feel more at ease. Helping each other, receiving one-on-one feedback and perceiving improvement in their linguistic mastery were furthermore mentioned as factors they felt boosted their enjoyment and so was developing friendships with L1 users. According to the interviewees, these aspects specifically increased their interest and enjoyment in using and learning the language and their eudaimonic happiness. The findings demonstrate that e-Tandem language learning can be a resource to enhance perceived enjoyment in foreign language learners at tertiary level and they illustrate that social and private components of FLE seem to be interlinked.